MENGEMBANGKAN POTENSI KECERDASAN SPIRITUAL ANAK MELALUI PROGRAM PONDOK ROMADHON DI DUSUN JURANG SEMPU DAYAKAN PONOROGO - Khusnul Khotimah (Journal of Islamic Science Community, 2022)
Given the importance of spiritual intelligence for individuals to find happiness and the true meaning of their lives, educators should recognize, understand, and develop this highest intelligence from an early age. With understanding and introduction from the beginning, it is hoped that character building efforts will produce a strong personal building as a foothold to build higher quality Indonesian human resources.